Modern Engineering Mathematics - James, Glyn; Dyke, Phil (Pearson International Content, 2020)
For first-year undergraduate modules in Engineering Mathematics.   Develop understanding and maths skills within an engineering context Modern Engineering Mathematics, 6th Edition by Professors Glyn James and Phil Dyke, draws on the teaching experience and knowledge of three co-authors, Matthew Craven, John Searl and Yinghui Wei, to provide a comprehensive course textbook explaining the mathematics required for studying first-year engineering. No matter which field of engineering you will go on to study, this text provides a grounding of core mathematical concepts illustrated with a range of engineering applications. Its other hallmark features include its clear explanations and writing style, and the inclusion of hundreds of fully worked examples and exercises which demonstrate the methods and uses of mathematics in the real world. Woven into the text throughout, the authors put concepts into an engineering context, showing you the relevance of mathematical techniques and helping you to gain a fuller appreciation of how to apply them in your studies and future career.   Also available with MyLab Math MyLab™ is the teaching and learning platform that empowers you to reach every student. By combining trusted author content with digital tools and a flexible platform, MyLab personalizes the learning experience and improves results for each student. MyLab Math for this textbook has over 1150 questions to assign to your students, including exercises requiring different types of mathematics applications for a variety of industry types. Learn more about MyLab Math.     Note: You are purchasing a standalone product; MyLab Math does not come packaged with this content. Students, if interested in purchasing this title with MyLab Math, ask your instructor to confirm the correct package ISBN and Course ID. Instructors, contact your Pearson representative for more information.  If you would like to purchase both the physical text and MyLab Math search for: 129233536X / 9781292335360 Modern Engineering Mathematics 6th Edition plus MyLab Math with eText -- Access Card Package  Package consists of: 1292253495 / 9781292253497 Modern Engineering Mathematics 6th Edition 1292253525 / 9781292253527 MyLab Math with Pearson eText -- Access Card -- for Modern Engineering Mathematics 6th Edition   Pearson, the world’s learning company.